Analysis of effect of the load force for a bevel gear tooth having straight direction - Bodzás, Sándor (Analecta Technica Szegedinensia, 2019)
Knowing of the geometric designing process of a straight bevel gear we have worked out a computer aided software with which this designing process could be eased. We have designed some bevel gear pairs having concrete geometry in the function of the modification of the number of teeth of the pinion and created the CAD (Computer Aided Designing) models of these gear pairs. After that the TCA (Tooth Contact Analysis) analysis could be followed. The load force have been situated on the top of the tooth edge on the tip circle. The established normal stress, normal elastic strain and normal deformation could be analyzed. Based on the results we can create the necessary diagrams and define the conclusions.